2021
DOI: 10.1016/j.aninu.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Maternal intake restriction programs the energy metabolism, clock circadian regulator and mTOR signals in the skeletal muscles of goat offspring probably via the protein kinase A-cAMP-responsive element-binding proteins pathway

Abstract: The biological mechanism by which maternal undernutrition increases the metabolic disorder risk of skeletal muscles in offspring is not fully understood. We hypothesize that maternal intake restriction influences metabolic signals in the skeletal muscles of offspring via a glucagon-mediated pathway. Twenty-four pregnant goats were assigned to the control group (100% of the nutrients requirement, n = 12) and restricted group (60% of the control feed allowance from pregnant days 45 to 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…But there is one direction worth mentioning. Zhou et al found that PGC-1α seems to play a role in the skeletal muscles of goats, and it can also maintain metabolic rhythm through the phosphorylation of upstream regulators [92]. We speculate that this is related to peroxisomal β-oxidation.…”
Section: Pgc-1αmentioning
confidence: 63%
“…But there is one direction worth mentioning. Zhou et al found that PGC-1α seems to play a role in the skeletal muscles of goats, and it can also maintain metabolic rhythm through the phosphorylation of upstream regulators [92]. We speculate that this is related to peroxisomal β-oxidation.…”
Section: Pgc-1αmentioning
confidence: 63%
“…Under postmortem anaerobic conditions in meat, hypoxic ischaemia leads to a series of increased glycolytic enzymes, such as fructose phosphate kinase, pyruvate kinase, and lactic dehydrogenase. Subsequently, this would promote pyruvate conversion into lactate, thereby decreasing the pH levels and inhibiting glycolytic enzyme activity (Lametsch et al, 2002;Zhou et al, 2021). The overall process will therefore stop the production of ATP by glycolysis.…”
Section: Muscle Ph and Adenosine Triphosphate Production Levelsmentioning
confidence: 99%
“…cAMP response element-binding protein is a member of the basic leucine zipper (bZIP) family of transcription factors and has the ability to stimulate PKA via the cAMP response element, thereby regulating the transcription of target genes ( Zhou et al, 2021 ). CREB is expressed in many tissues and plays a very important regulatory role in the nervous system.…”
Section: Transcription Factorsmentioning
confidence: 99%